Systematic tuning of rhodamine spirocyclization for super-resolution microscopy - Lardon, Nicolas; Wang, Lu; Tschanz, Aline; Hoess, Philipp; Tran, Mai; D'Este, Elisa; Ries, Jonas; Johnsson, Kai (Journal of the American Chemical Society, 2021)
Rhodamines are the most important class of fluorophores for applications in live-cell fluorescence microscopy. This is mainly because rhodamines exist in a dynamic equilibrium between a fluorescent zwitterion and a nonfluorescent but cell-permeable spirocyclic form. Different imaging applications require different positions of this dynamic equilibrium, and an adjustment of the equilibrium poses a challenge for the design of suitable probes. We describe here how the conversion of the ortho-carboxy moiety of a given rhodamine into substituted acyl benzenesulfonamides and alkylamides permits the systematic tuning of the equilibrium of spirocyclization with unprecedented accuracy and over a large range. This allows one to transform the same rhodamine into either a highly fluorogenic and cell-permeable probe for live-cell-stimulated emission depletion (STED) microscopy or a spontaneously blinking dye for single-molecule localization microscopy (SMLM). We used this approach to generate differently colored probes optimized for different labeling systems and imaging applications.